Malignant mixed mullerian tumour: A brief communication - Malla, Dibya S; Vaidya, Achala; Kumar, Prabhaker (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Carcinosarcoma is a Malignant mixed mullerian tumor (MMT) originating from the mesothelium and mesenchyme of embryonic mesoderm, now better established by electron microscopy and immuno-peroxidase techniques. The most interesting aspects in the histogenesis of this biphasic tumour mostly monoclonal in origin are briefly communicated in this paper. Unfortunately, no adjuvant chemo or radiotherapy for either persistent or recurrent malignant diseases has ever resulted in cure of this aggressive tumour, usually seen in menopausal women. Key words: Malignant mixed mullerian tumor (MMT), carcinosarcoma, menopause. doi:10.3126/njog.v2i1.1484 N. J. Obstet. Gynaecol Vol. 2, No. 1, p. 74 - 78 May -June 2007